Effects of δ mesons on baryonic direct Urca processes in neutron star matter - 黄修林 王海军 刘广洲 刘承志 许妍 (Chinese physics C, 2015)
This study investigates the relativistic neutrino emissivity of the nucleonic and hyperonic direct Urca processes in the degenerate baryon matter of neutron stars, within the framework of relativistic mean field theory. In particular, we study the influence of the isovector scalar interaction on the nucleonic and hyperonic direct Urca processes by exchanging δ mesons. The results indicate that δ mesons lead to obvious enhancement of the total neutrino emissivity, which must result in a more rapid cooling rate of neutron star matter.